Design and analysis of flexible bow-tie antenna for medical application - Othman, N.; Samsuri, N. A.; A. Rahim, M. K.; Kamardin, K. (ELEKTRIKA- Journal of Electrical Engineering, 2017)
This research presents an extensive investigation and analysis of bow-tie antenna performance made of three different flexible materials as the substrates. The antenna performance is address in terms of S11 and radiation pattern. The flexible antenna performance is simulated in free space condition and compared to the antenna performance in on-body environment. The aim of this research is to choose suitable flexible dielectric substrate which sustains its performance under on-body environment. The results of this research could provide guidance and has significant implication for future development of wearable electronics especially in medical monitoring application.